Motivation And Commitment Young Children's Swimming Training - Berlianty Sarmidi, Firda; Komarudin, Komarudin; Yamin Saputra, Mochamad; Novian, Geraldi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Swimming athletes must be committed to their training, especially those who are still young. However, not all young swimmers are entirely committed to their training. As a result, the purpose of this study is to link a young swimmer’s motivation with a commitment they make throughout training. The quantitative descriptive method was utilized in this study, and data was collected utilizing total sampling procedures. The population and sample used were young swimmers aged 13–17, while the indicators used were the adoption of the sport commitment scale and motivation level. The Pearson correlation test yielded Sig results. (2-tailed) = 0.625, which is larger than 0.05, indicating that the two variables are unrelated. The conclusion is that a swimmer’s training commitment is not necessarily determined by their motivation. Because the majority of these young swimmers are self-motivated, they are less likely to develop burnout during training.